Graveoline, an antimicrobial activ alkaloid from Ruta angustifolia (L.) Pers. and its in vitro antimicrobial combination effects with either erythromycin or vancomycin - Mohd Kamal, Laina Zarisa; Mohd Hassan, Norazian; Md Taib, Nurhaya; Khin Soe, May (2017)
Ruta angustifolia (L.) Pers. is a Rutaceous species which contains various anthranilic acid derived alkaloids including the bioactive quinolones. This study is aimed at identifying the antimicrobial active natural quinolones of R. angustifolia and evaluating their potential as synergistic enhancers in alkaloid-antibiotic combinations. Antimicrobial bioautography-guided isolation of alkaloidal fractions of R. angustifolia leaves has led to the identification of 1-methyl-2-[3’,4’-methylenedioxyphenyl]-4-quinolone [graveoline], (III) as the major antimicrobial active alkaloid together with 2,3-dimethoxy-1-hydroxy-10-methylacridone [arborinine], (I) and 4,7,8-trimethoxyfuro [2,3-b]quinoline [skimmianine], (II). Alkaloid III and I showed Minimum Inhibitory Concentration (MIC) values ranging from 250 µg/ml to 1000 µg/ml against Staphylococcus aureus ATCC 25923, Enterococcus fecalis ATCC 29212 and Escherichia coli ATCC 25922. Checkerboard assay for antimicrobial combination effects between alkaloid III with either erythromycin or vancomycin showed enhancement of the antimicrobial activity of both antibiotics with Fractional Inhibitory Concentration Index (FICI) ranged from 0.37 to 1.50. Synergistic effect with FICI of 0.37 was observed for III-erythromycin combination against S. aureus compared to FICI of 1.00 for ciprofloxacin-erythromycin indifference effect. Alkaloid III was a potential candidate for antimicrobial combination agent especially against S. aureus which supports the idea of using plant metabolites as antimicrobial synergistic agents.